2010
DOI: 10.1186/1752-1947-4-101
|View full text |Cite
|
Sign up to set email alerts
|

Enteritis caused by Campylobacter jejuni followed by acute motor axonal neuropathy: a case report

Abstract: Introduction: Campylobacter species represent the main cause of bacterial diarrhea in developed countries and one of the most frequent causes of enterocolitis in developing ones. In some patients, Campylobacter jejuni infection of the gastrointestinal tract has been observed as an antecedent illness of acute motor axonal neuropathy, a variant of Guillain-Barré syndrome. Case presentation: We present a case of acute motor axonal neuropathy following infection with Campylobacter jejuni subspecies jejuni, biotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Campylobacter jejuni is considered to be a commensal organism of chicken gut [37] and the leading causative agent of gastroenteritis in humans worldwide [38]. Although the experimental infection of chickens with C. jejuni can lead to diarrhea, chickens sometimes can develop severe paralysis resembling neuropathy [22, 39].…”
Section: Association Of C Jejuni With Gbs and Its Subtypesmentioning
confidence: 99%
“…Campylobacter jejuni is considered to be a commensal organism of chicken gut [37] and the leading causative agent of gastroenteritis in humans worldwide [38]. Although the experimental infection of chickens with C. jejuni can lead to diarrhea, chickens sometimes can develop severe paralysis resembling neuropathy [22, 39].…”
Section: Association Of C Jejuni With Gbs and Its Subtypesmentioning
confidence: 99%
“…Some species definitely cause human disease. C.jejuni is one of the most important food-borne pathogen in the world, and its infection is a leading cause of acute bacterial diarrhea in humans in many developed countries [12], [13]. Campylobacter coli , Campylobacter upsaliensis , and Campylobacter lari are also associated with human gastroenteritis [6], [7], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of reactive arthritis usually occur around 14 days after infection (range, 3 days to 6 weeks). Some investigations revealed that the percentage of patients with confirmed C. jejuni infection who develop ReA range from 0.7%, (1.8%, 2.0%, 2.6%, 7%,) to 30% (Ristić, 2010). A population study in southern Finland found that 7% of the participants developed ReA and 1% developed reactive tendinitis, enthesopathy or bursitis (Hannu et al, 2002).…”
Section: Clinical Presentations Of Campylobacter Infectionsmentioning
confidence: 99%